Ecological Analysis of Megabenthos in Coral Reef Ecosystems of The Waters Surrounding Bahoi Village, North Minahasa Regency - Grathia Charity; Manembu, Indri S.; Mamangkey, N. Gustaf F.; Rumengan, Antonius P.; Boneka, Farnis B.; Tilaar, Sandra O. (JURNAL PESISIR DAN LAUT TROPIS, 2026)
Megabenthos are a group of organisms larger than 1 cm that inhabit the seafloor and are sensitive to environmental changes. Information regarding megabenthos in Bahoi Village has not yet been published; therefore, this study was conducted to fill the data gap related to benthic community structure in the area. Data were collected at three stations representing different levels of ecological pressure using the Benthos Belt Transect  method, with a transect length of 70 m and an observation width of 2 m, resulting in a total surveyed area of 140 m² per station. Target megabenthos recorded included Diadema spp., Linckia laevigata, Tridacninae, and Drupella cornus. Based on the analysis, Station 1 (near settlement and non-MPA) showed densities of Diadema spp. of 2.11 ind/m², Linckia laevigata of 0.04 ind/m², Tridacninae of 0.03 ind/m², and Drupella cornus of 0.07 ind/m², with H’ = 0.29, C = 0.88, and E = 0.2. Station 2 (MPA) recorded densities of Diadema spp. of 0.007 ind/m², Linckia laevigata of 0.029 ind/m², Tridacninae of 0.014 ind/m², and Drupella cornus of 0.014 ind/m², with H’ = 1.27, C = 0.30, and E = 0.9. Station 3 (far from settlement and non-MPA) showed densities of Linckia laevigata of 0.19 ind/m² and Diadema spp. of 0.07 ind/m², with H’ = 0.58, C = 0.61, and E = 0.8. The patterns of ecological indices indicate a strong relationship between the intensity of human intervention and habitat characteristics in determining the stability of megabenthic communities. Keywords: megabenthos, coral reefs, community, benthos belt transect, Bahoi Village   Abstrak Megabentos merupakan kelompok organisme yang hidup di dasar laut dan berukuran lebih dari 1 cm yang sensitif terhadap perubahan lingkungan. Informasi mengenai megabentos di Desa Bahoi hingga kini belum dipublikasikan sehingga penelitian ini dilakukan untuk mengisi kesenjangan data terkait struktur komunitas bentik di wilayah tersebut. Pengumpulan data dilakukan pada tiga stasiun yang mewakili perbedaan tingkat tekanan ekologis menggunakan metode Benthos Belt Transect sepanjang 70 m dengan lebar pengamatan 2 m sehingga total area pengamatan 140 m² per stasiun. Megabentos target yang ditemukan meliputi Diadema spp., Linckia laevigata, Tridacninae, dan Drupella cornus. Berdasarkan analisis data, Stasiun 1 (dekat permukiman & non-DPL) memiliki kepadatan Diadema spp. sebesar 2,11 ind/m², Linckia laevigata sebesar 0,04 ind/m², Tridacninae sebesar 0,03 ind/m² dan Drupella cornus sebesar 0,07 ind/m² dengan H’=0,29, C=0,88, dan E=0,2. Stasiun 2 (DPL) memiliki kepadatan Diadema spp. sebesar 0,007 ind/m², Linckia laevigata sebesar 0,029 ind/m², Tridacninae sebesar 0,014 ind/m² dan Drupella cornus sebesar 0,014 ind/m² dengan H’=1,27, C=0,3 dan E=0,9. Stasiun 3 (jauh dari permukiman & non-DPL) memiliki kepadatan Linckia laevigata sebesar 0,19 ind/m² serta Diadema spp. sebesar 0,07 ind/m² dengan H’=0,58, C=0,61 dan E=0,8. Pola indeks ekologi menunjukkan hubungan kuat antara tingkat tekanan intervensi manusia dan karakteristik habitat terhadap stabilitas komunitas megabentos. Kata kunci: megabentos, terumbu karang, komunitas, benthos belt transect, Desa Bahoi